The Performance of the Adiwiyata Program: An Evaluation Study at Madrasah Tsanawiyah Negeri - Masdar, Masdar; K, Nurdin; Kamal, Helmi (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palopo), 2024)
Environmental challenges, such as climate change, pollution, and deforestation, require proactive educational strategies to foster sustainability awareness and responsible behavior among students. The Adiwiyata Program, introduced by the Indonesian Ministry of Environment and Forestry, aims to integrate environmental education into the school curriculum to promote sustainable practices. This study evaluates the implementation of the Adiwiyata Program at MTs Negeri Luwu Timur using the CIPP (Context, Input, Process, Product) evaluation model. The research adopts a qualitative approach, utilizing observations, semi-structured interviews with school administrators, teachers, students, and community members, and document analysis to assess the program's effectiveness. The findings reveal that the program aligns well with the school’s vision and mission, emphasizing academic excellence and environmental stewardship. Strong government support and active community engagement significantly contribute to the program's success. Adequate resources, including well-trained educators and interdisciplinary curriculum integration, have increased environmental awareness, positive behavioral changes among students, and noticeable improvements in the school’s physical environment. However, challenges such as limited funding, delayed external resource fulfillment, and difficulties in engaging new students highlight areas for improvement. This study concludes that the Adiwiyata Program at MTs Negeri Luwu Timur effectively integrates environmental education in madrasahs. The research offers strategic recommendations for enhancing program sustainability, improving stakeholder collaboration, and expanding the program’s impact beyond the school community. These findings contribute to the broader discourse on environmental education and its role in fostering sustainable development in educational institutions.